2016
DOI: 10.1061/(asce)hz.2153-5515.0000232
|View full text |Cite
|
Sign up to set email alerts
|

Commuter Exposure to Air Pollution in Newcastle, U.K., and Mumbai, India

Abstract: Results of a study on commuter exposure to carbon monoxide (CO) and PM10 during transit in the several commonly popular modes of transport in Mumbai, India and Newcastle, UK are presented in this paper. In Mumbai, real-time exposure concentrations were measured whilst commuting along a route by bus, train, air conditioned taxi and a non-air-conditioned private car. In Newcastle, real-time exposure concentrations were measured whilst travelling by electric vehicle, public bus and bicycle along a route. Average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Furthermore, Onat et al 41 found that UFP levels were 80% higher in vehicles when WO and they were more than doubled in Moreno et al 28 study in the same condition. This pattern is not limited to UFP but also affects different TRAP such as PM 10 , PM 2.5 , CO, NO 2, and sulfur dioxide (SO 2 ) 31,35,42‐44 …”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, Onat et al 41 found that UFP levels were 80% higher in vehicles when WO and they were more than doubled in Moreno et al 28 study in the same condition. This pattern is not limited to UFP but also affects different TRAP such as PM 10 , PM 2.5 , CO, NO 2, and sulfur dioxide (SO 2 ) 31,35,42‐44 …”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Parisian taxi drivers were exposed to lower CO levels (0.42 ± 0.83 ppm) than in a previous study conducted 20 years ago (3.8 ± 1.7 ppm) 26 . In Parisian taxis, CO levels were also the lowest compared with those measured in India (5.33 ± 0.68 ppm), 24 in China (5.21 ± 1.52 ppm), 17 in Iran (19.84 ppm), 25 and in the United Kingdom (1.05 ± 0.44 ppm) 18 . This is probably due to the evolution of emission regulations and technological improvements over the years 38 .…”
Section: Discussionmentioning
confidence: 51%
“…There are relatively few studies assessing taxi drivers’ exposure to air pollutants inside their vehicles even though they are at particular risk of higher pollutant intake 16 . Results have indicated that air pollutants inside taxicabs originated mainly from surrounding vehicles 17‐20 and smoking in cars, 21,22 and varied according to ventilation settings 19,20,23,24 and meteorological parameters 16‐18,22,25,26 . In 2000, Zagury et al 26 showed that 29 Parisian taxi drivers were exposed to high pollutant concentrations inside their vehicles compared with their urban background levels: carbon monoxide (CO): 3.8 ± 1.7 vs 1 ± 0.46 ppm; nitrogen monoxide (NO): 625 ± 223 vs 55 ± 30 µg/m 3 ; nitrogen dioxide (NO 2 ): 139 ± 43 vs 72 ± 22 µg/m 3 ; and black smoke (BS): 168 ± 53 vs 44 ± 29 µg/m 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies have been conducted to compare the exposure levels of air pollutants among different modes of commuters including car, bus or ferry commuters, bicycle riders, and pedestrians, and most with conflicting results (Badland and Duncan 2009;Chertok et al 2004;Farrar et al 2001;Knibbs and de Dear 2010). The inconsistency in the study's results were due to various reasons including small sample size, differences in research design, trip mode, choice of route and type of equipment used to measure air pollution (Knibbs et al 2011;Namdeo et al 2016;Xie et al 2017). One of the best examples is the study conducted by Hunter et al (2012) in Australia who measured exposure to particle-number concentrations among cyclists in Brisbane.…”
Section: Introductionmentioning
confidence: 99%